Pengaruh Ekuitas Merek Terhadap Keputusan Pembelian Konsumen Pada Produk iPhone di Kota Surabaya - Heri Susanto, William (Rifa'Institute, 2022)
People's interest in technology, or brands, has always been very important. Therefore, technological developments increase the number of new products and competitors in the telecommunications industry, placing consumers first and consumers with more choices and information as king. In this era, telecommunications has also become a competitive business field for business actors because of its extraordinary potential. This situation causes competition between companies, and players find themselves needing to maximize their company's wealth to survive from companies that manufacture smartphone products. One way to achieve this state is BRAND. Kotler explains that a brand is very useful in identifying the goods or services of one publisher or group of publishers, distinguishing them from similar products from other publishers. For them, for every company, the 'brand' is everything that makes it up and the most important capital. Because it is the basis of competitive advantage and future source of income. In this study, we adopted the method of using a questionnaire based on the results obtained. Brand loyalty therefore receives the most dominant value in purchasing decisions. iPhone consumer loyalty has a significant effect on consumer purchasing decisions. As a result of this research, we can come to the conclusion that iPhone users often give consumers positive feedback.